Documento, poder e governo: os agenciamentos políticos na construção patrimonial no Arquivo Central do IPHAN/Seção Rio de Janeiro - Grigoleto, Maira Cristina [UNESP] (2013)
This thesis proposes to address issues surrounding the documentary practices within the Brazilian policies for patrimony having two propositions as principles: the patrimonial documentation as social device of patrimony's power; and the patrimony's field as space to articulate the relations and strategic games of power from the state. Bringing this discussion to the specific place of the Central Archives from IPHAN/Rio de Janeiro Section (ACI/RJ), our purpose is to explain how these associations are established within a calculus' center touting the tensions between knowledge and power to produce materialities, stabilities and permanencies. Thus, in first place, we propose the understanding of the document's thought to perceive it as an emergency due to various institutional negotiations established historically through regimes of power/knowledge and of knowledge/power. In a second moment, we treat construction of patrimonial knowledge and configuration of patrimonial documentation as a power device in the interior of governmental practices and policies. In this way, we trace a way to understand the disputes of knowledge/power between neo-colonials and neomodernists for the constitution and development of the legal patrimonial field in Brazil. Subsequently, we revisit the notion of archive pointing to the materiality and the documenting process. Finally, we show the formation, structure and operation of the Central Archives from IPHAN/Rio de Janeiro Section (ACI/RJ) to analyze it as a calculus' center and, consequently, as a place practitioner and practiced.